Widowhood and Life Satisfaction Among Chinese Elderly Adults: The Influences of Lifestyles and Number of Children - Yang, Caiyun; Sun, Xixi; Duan, Wenjie (Frontiers in Public Health, 2022)
Our study examined how lifestyle and number of children influence the relationship between widowhood and life satisfaction based on self-regulation theory. A sample of 2,911 older respondents (male = 1,492, female = 1,419, mean age = 69.12 years, SD = 7.25) participated in the Chinese General Social Survey. Our findings suggest that lifestyle is positively related to life satisfaction, and number of children is positively associated with life satisfaction but negatively related to lifestyle. The moderated mediation model demonstrated that lifestyle partly mediated the relationship between widowhood and life satisfaction. Moreover, number of children moderated the relationship between widowhood and lifestyle and between lifestyle and satisfaction with life. Widowed older individuals who have more children are likely to show a higher level of satisfaction with life. The present study has significance in practice because it provides empirical implications obtained from a national survey on the universal two-child policy in China.